2002
DOI: 10.1248/cpb.50.229
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Behavior of Sitafloxacin, Fluoroquinolone Antibiotic, in an Aqueous Solution.

Abstract: Sitafloxacin hydrate (STFX hydrate: (Ϫ)-7-[(7S)-1) Fluoroquinolones are important synthetic antimicrobial agents and they have been widely used as therapeutic agents for general bacterial infectious diseases. However, some fluoroquinolones are known to induce phototoxicity as a side effect.2) A large number of studies have been reported to elucidate the mechanism of phototoxicity of fluoroquinolones. We reported that carbon centered radical (· C), hydroxyl radical (· OH), and singlet oxygen ( 1 O 2 ) are gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 8 publications
2
13
0
2
Order By: Relevance
“…It was found that SPA was more sensitive to light in the zwitterionic form and more stable in the acidic region. With respect to wavelength dependence the conclusion was that SPA was more labile at the maximum absorption wavelength [47]. Overall, these results demonstrate that dehalogenation at position 8 is a significant photodegradation mechanism for these fluoroquinolones.…”
Section: Physicochemical Properties and Stability Of Fluoroquinolonesmentioning
confidence: 70%
See 2 more Smart Citations
“…It was found that SPA was more sensitive to light in the zwitterionic form and more stable in the acidic region. With respect to wavelength dependence the conclusion was that SPA was more labile at the maximum absorption wavelength [47]. Overall, these results demonstrate that dehalogenation at position 8 is a significant photodegradation mechanism for these fluoroquinolones.…”
Section: Physicochemical Properties and Stability Of Fluoroquinolonesmentioning
confidence: 70%
“…One of the major drawbacks of fluoroquinolones is their photosensitivity. It has been proposed that a high degree of halogenation may lead to low photostability and, consequently, to the formation of photoproducts that can induce adverse effects and toxicity [47,74,75]. Therefore, a considerable interest has arisen in the investigation of the process of degradation.…”
Section: Physicochemical Properties and Stability Of Fluoroquinolonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Knapp et al [11] found that enrofloxacin photodegraded rapidly following first order kinetics and was transformed into ciprofloxacin in sunlit mesocosms. Araki et al [13] found that sitafloxacin photodegradation also followed first-order kinetics, and the photolytic rate was affected by the matrix pH and Cl − . In previous studies, such aqueous photoreactive dissolved matter as Fe(III), NO 3 − and humic acids (HA) was shown to have significant impacts on the photochemical reaction kinetics and pathways of organic pollutants in surface waters [14−16].…”
mentioning
confidence: 99%
“…Araki et al (1) reported that a carbon-centered radical ( ⅐ C) was generated at position 8 by scission of the COCl bond of an 8-chloro quinolone under UV irradiation, and excess chloride ions immediately reacted with it. As a result, the COCl bond was recovered and the apparent photostability was increased.…”
Section: Discussionmentioning
confidence: 99%